Remote intervention engagement and outcomes in the Clinical Trials in Organ Transplantation in Children consortium multisite trial. Issue 9 (12th April 2021) - Duncan‐Park, Sarah; Dunphy, Claire; Becker, Jacqueline; D'Urso, Christine; Annunziato, Rachel; Blatter, Joshua; Conrad, Carol; Goldfarb, Samuel B.; Hayes, Don; Melicoff, Ernestina; Schecter, Marc; Visner, Gary; et al.
Abstract : Remote interventions are increasingly used in transplant medicine but have rarely been rigorously evaluated. We investigated a remote intervention targeting immunosuppressant management in pediatric lung transplant recipients. Patients were recruited from a larger multisite trial if they had a Medication Level Variability Index (MLVI) ≥2.0, indicating worrisome tacrolimus level fluctuation. The manualized intervention included three weekly phone calls and regular follow‐up calls. A comparison group included patients who met enrollment criteria after the subprotocol ended. Outcomes were defined before the intent‐to‐treat analysis. Feasibility was defined as ≥50% of participants completing the weekly calls. MLVI was compared pre‐ and 180 days postenrollment and between intervention and comparison groups. Of 18 eligible patients, 15 enrolled. Seven additional patients served as the comparison. Seventy‐five percent of participants completed ≥3 weekly calls; average time on protocol was 257.7 days. Average intervention group MLVI was significantly lower (indicating improved blood level stability) at 180 days postenrollment (2.9 ± 1.29) compared with pre‐enrollment (4.6 ± 2.10), p  = .02. At 180 days, MLVI decreased by 1.6 points in the intervention group but increased by 0.6 in the comparison group ( p  = .054). Participants successfully engaged in a long‐term remote intervention, and their medication blood levels stabilized. NCT02266888. Abstract : This multisite trial evaluates a remote intervention targeting medication adherence in pediatric lung transplant recipients, finding that patients and their families can be successfully engaged over a long follow‐up period and that the intervention stabilizes medication blood levels.